(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Freedom of Belief, Adequate Food and Ritual Slaughter in Market Requirement. Reflections on the Rejection of the Ordinance Amending Ritual Killing of Animals, adopted by the Brussels Parliament in June 2022. In June 2022 the Parliament of the Brussels Region rejected a proposal for an ordinance aimed at banning the possibility of killing animals according to religious standards, as previously done by the Region of Wallonia and Flanders, similar to how some European countries have done. It is an opportunity to carry out a survey on which countries allow and do not allow ritual slaughter in Europe and the underlying reasons. Thus, a minimum common denominator emerges between the countries that protect this confessional instance of some religious minorities, determined by market reasons. A new configuration of the principle of religious freedom is therefore emerging as the right to access adequate food in line with the confessional dictates of ritual slaughter, according to a particular declination aimed at the economic sustainability of producers and consumers, also in terms of food safety.